Pink triangle legacies : coming out in the shadow of the Holocaust - Newsome, W. Jake 1987- (Cornell University Press, 2022)
Introduction : "Beaten to Death, Silenced to Death" -- "They are Enemies of the State!" : The Fate of LGBTQ People in Nazi Germany -- "For Homosexuals, the Third Reich Hasn't Ended Yet" : Paragraph 175 and the Nazi Past in West Germany -- "The Only Acceptable Gay Liberation Logo" : The Reclamation of the Pink Triangle in West Germany -- "It's a Scar, But In Your Heart" : The Pink Triangle in American Gay Activism -- "Remembrances of Things Once Hidden" : Piecing Together the Pink Triangle Past on Stage and on Page -- "We Died There, Too" : Commemoration and the Construction of a Transatlantic Gay Identity -- Epilogue : "Remembering Must Also Have Consequences.